The relationship between urine specific gravity, urine pH, and blood uric acid levels to the type of urinary stones of patients with urolithiasis at Sanglah Hospital, Bali, Indonesia - Jetty Kalembang; Anak Agung Gde Oka; I Gede Raka Widiana (Intisari Sains Medis, 2020)
Background: Urine specific gravity, urine pH, and blood uric acid levels are risk factors for urinary tract stones. The urinary tract stones are formed due to the concentration of a solute exceeds its ability to remain in solution, resulting in supersaturation and crystallization. This study aims to determine the relationship between urine specific gravity, urine pH, and blood uric acid levels to the urinary stone's types in patients with urolithiasis at Sanglah HospitalMethods: A retrospective cross-sectional study was conducted among 95 subjects by using secondary data from the medical records in the period June 2017-2018 at Sanglah Hospital. The urolithiasis patient who met the inclusion and exclusion criteria were enrolled in this study. Data were analyzed by the Mann-Whitney Test and Kruskal-Wallis Test using SPSS version 17 for Windows.Results: The average age was 55Â±11 years old. Most of respondents were male (70.5%), normal Body Mass Index (BMI) (89.5%), urine pH <7 (75.7%), and mixed type of urinary stones (48.4%). There was a statistically significant relationship between the type of uric acid stone (p=0.029), blood uric acid levels (p=0.003), phosphate stone type (p=0.026), and magnesium stone (p=0.010) with urine pH. Besides, there was a statistically significant relationship between ammonium stone and blood uric acid levels types (p=0.022). A statistically significant difference was also found between stone types based on urine pH (p=0.013) in multivariate analysis.Conclusion: There is a significant relationship between urine pH and stone type on the incidence of urolithiasis in Sanglah Hospital in June 2017-2018, thereby increasing the incidence of urolithiasis.